The potential exceptional role of a small Baltic boulder reef as a solitary habitat in a sea of mud. Issue 2 (10th January 2019) - Beisiegel, Kolja; Tauber, Franz; Gogina, Mayya; Zettler, Michael L.; Darr, Alexander
Abstract: In this study, non‐destructive seafloor imaging techniques were employed to assess the benthic community structure of a recently discovered boulder reef within the central Arkona Basin of the Baltic Sea. Data indicate that geographical isolation, water column stratification and temporary oxygen deficiency create an exceptional reef habitat in a sea of mud. The reef forms a saline refuge for the deepest and easternmost known population of the plumose sea anemones ( Metridium dianthus Ellis, 1768) in the Baltic Sea. Limited connectivity to other reefs and dominance of the aggressively colonizing and planktivorous M. dianthus hamper the recruitment of other species and lead to an overall low invertebrate richness. Large boulders attract ecologically and economically important fish like Baltic cod ( Gadus morhua Linnaeus, 1758) that find shelter in the otherwise heavily fished Arkona Basin. Despite this very first exploration being only a snapshot of the observed community, findings imply a potential conservation importance of this Germany's deepest known natural habitat type 1170 ('reefs').